Ocular perfusion pressure and ocular blood flow in glaucoma - Cherecheanu, A Popa (Elsevier Science Ltd, 2013)
Glaucoma is a progressive optic neuropathy of unknown origin. It has been hypothesized that a vascular component is involved in glaucoma pathophysiology. This hypothesis has gained support from studies showing that reduced ocular perfusion pressure is a risk factor for the disease. The exact nature of the involvement is, however, still a matter of debate. Based on recent evidence we propose a model including primary and secondary insults in glaucoma. The primary insult appears to happen at the optic nerve head. Increased intraocular pressure and ischemia at the post-laminar optic nerve head affects retinal ganglion cell axons. Modulating factors are the biomechanical properties of the tissues and cerebrospinal fluid pressure. After this primary insult retinal ganglion cells function at a reduced energy level and are sensitive to secondary insults. These secondary insults may happen if ocular perfusion pressure falls below the lower limit of autoregulation or if neurovascular coupling fails. Evidence for both faulty autoregulation and reduced hyperemic response to neuronal stimulation has been provided in glaucoma patients. The mechanisms appear to involve vascular endothelial dysfunction and impaired astrocyte-vessel signaling. A more detailed understanding of these pathways is required to direct neuroprotective strategies via the neurovascular pathway.